Triphenylmethane derivatives have high in vitro and in vivo activity against the main causative agents of cutaneous leishmaniasis. - Renata Celi Carvalho de Souza Pietra; Lucas Fonseca Rodrigues; Eliane Teixeira; Levi Fried; Benjamin Lefkove; Ana Rabello; Jack Arbiser; Lucas Antônio Miranda Ferreira; Ana Paula Fernandes (PLoS ONE)
The current standard of care for cutaneous leishmaniasis (CL) is organic antimonial compounds, but the administration of these compounds is complicated by a low therapeutic - toxic index, as well as parenteral administration. Thus, there is an urgent need for the development of new and inexpensive therapies for the treatment of CL. In this study, we evaluate the activity of the triphenylmethane (TPM) class of compounds against three species of Leishmania which are pathogenic in humans. The TPM have a history of safe use in humans, dating back to the use of the original member of this class, gentian violet (GV), from the early 20(th) century. Initially, the in vitro efficacy against Leishmania (Viannia) braziliensis, L. (Leishmania) amazonensis and L. (L.) major of 9 newly synthesized TPM, in addition to GV, was tested. Inhibitory concentrations (IC) IC(50) of 0.025 to 0.84 µM had been found in promastigotes in vitro assays. The four most effective compounds were then tested in amastigote intracellular assays, resulting in IC(50) of 0.10 to 1.59 µM. A high degree of selectivity of antiparasitic activity over toxicity to mammalian cells was observed. Afterwards, GV and TPM 6 were tested in a topical formulation in mice infected with L. (L.) amazonensis leading to elimination of parasite burdens at the site of lesion/infection. These results demonstrated that TPM present significant anti-leishmanial activities and provide a rationale for human clinical trials of GV and other TPM. TPM are inexpensive and safe, thus using them for treatment of CL may have a major impact on public health.